Study of risk factors in post-laparotomy wound dehiscence - Verma, Siddharth; Patil, Sagar Manohar; Bhardwaj, Ankur (International Surgery Journal, 2018)
Background: Wound dehiscence/burst abdomen is a very serious post-operative complication associated with high morbidity and mortality. The need for this study is to highlight the risk factors for wound dehiscence and remedial measures to prevent or reduce the incidence of wound dehiscence. This will certainly reduce mortality and morbidity in the form of prolonged hospital stay, increased economic burden on health care resources. Methods: This is a prospective and observational study involving all those who have developed abdomen wound dehiscence after initial surgery, an elaborative study of these cases with regard to date of admission, clinical history regarding the mode of presentation, significant risk factors, investigations, time of surgery and type of surgery postoperatively, study of diagnosis and day of diagnosis of wound dehiscence is done till the patient is discharged from the hospital. The collected data is analysed and statistics were made according to need. Results: The incidence of abdominal wound dehiscence is more common in male patients in 4th to 5th decade. Patients with peritonitis due to duodenal perforation, complicated appendicitis, pyoperitoneum and intestinal obstruction and carried higher risk of abdominal wound dehiscence. Abdominal wound dehiscence was more common in patients operated in emergency. Patients with intra-abdominal infection, anaemia, hypoalbuminemia, jaundice had higher incidence of wound dehiscence. Conclusions: Wound dehiscence can be prevented by improving nutritional status of patient, proper surgical technique, controlling infections and correcting co-morbid conditions.